A Discussion on Chinese Road of NGOs : Reform and Co-governance by Society - Wang, Ming (Research series on the Chinese dream and China's development path., 2017)
This book reflects the author's views on NGO development in China and includes recent papers, reviews, and policy suggestions he has written. This collection introduces the current state of research on NGOs and their development in China to an English-speaking audience, allowing them to understand China's social reforms, which center on NGOs.